Léxico empleado en los titulares de medios impresos: Caso Diario Extra. primer trimestre 2019 - Vera Pesantes, Rudy Jazmin (2019)
The present study whose theme is the influence of the lexicon used in the owners of print media: Extra Daily case. It takes place in the city of Babahoyo, during the first half of 2019, because this newspaper is sold a lot in this town, and despite the fact that the number of pages is not excessive, let alone the news is cultural, readers they are often carried away by the impact of the words used in their headlines. That is why the objective of the study is to determine the influence of the lexicon used in the headlines of print media: Extra Journal case, to determine the problem began by observing and monitoring the newspaper headlines, during the months of January, February and March 2019, to establish the style they use in this medium. Then this style was analyzed, in relation to the Law of communication, as well as the relationship with the Code of Ethics of the Journal, the surveys were also applied to the Readers, to analyze their opinions and their reactions to the way in which Diario Extra presents News. All this led to a general conclusion, that evidently the lexicon used motivates people to buy the newspaper, which awakens in them feelings of curiosity, morbidity, fear, with which interest is aroused, and a low cultural level of the readers, which in general terms and according to the results of the investigation, belong to a low social stratum and this is taken advantage of by the newspaper's editorial group